Promising Anti-Wrinkle Applications of Aromatic Extracts of Hedychium coronarium J. Koenig via Antioxidation and Collagenase Inhibition - Pattiya Tammasorn; Wannaree Charoensup; Anurak Bunrod; Watchara Kanjanakawinkul; Wantida Chaiyana (MDPI AG, 2023)
This study aimed to extract aromatic compounds from the rhizomes, leaf sheaths, and leaves of Hedychium coronarium and investigate their chemical compositions, cosmetic/cosmeceutical activities, and irritation potency. The chemical compositions were investigated via gas chromatography-mass spectrometry. The antioxidant activities were evaluated via spectrophotometry. The anti-skin wrinkle properties were investigated via collagenase, elastase, and hyaluronidase inhibition. The irritation potency was observed via a hen's egg-chorioallantoic membrane test. Eucalyptol was detected as a major component in the rhizomes and leaf sheaths, while β-caryophyllene was predominant in the leaves. The absolutes from the rhizomes were the strongest antioxidants, with ABTS scavenging properties similar to L-ascorbic acid. Interestingly, the equivalent concentration (EC1) of the absolute from the rhizome was 0.82 ± 0.01 µg FeSO4/g extract, which was significantly more potent than L-ascorbic acid (0.43 ± 0.03 µg FeSO4/g extract). The rhizome-derived absolute was the most effective against collagenase, while the concretes from the rhizomes and leaf sheaths showed promising anti-hyaluronidase activity with inhibitions of 90.5 ± 1.6% and 87.4 ± 5.1%, respectively. The irritability of the aromatic extracts was not different from that of the vehicle control, proving their safety. Therefore, the Hedychium coronarium rhizome-derived absolute was an attractive and potent antioxidant with anti-collagenase activities, indicating its potential for use in anti-aging formulations.